Crazy like a fox : adventures in schizophrenia - Furnas, Christi (Street Noise Books, 2024)
"I created Fox Foxerson, a gender neutral protagonist faced with the onset of an unfamiliar mental illness. Fox battles symptoms and tries to stay employed. Fox navigates the health care system labyrinth and attempts to maintain friendships, even as defining "reality" becomes a challenge. In the realm of fiction, Fox can tell my adventures while I stay free to have fun with my characters: Sock Puppet Doctor, Jellyfish Boss-lady, Goth Fairy, monsters and such. My goal for Fox is that by presenting a string of easily identifiable moments, I am able to bring folks into the totality of an experience that they might not otherwise imagine. My goal is to keep the story accessible. When Fox is experiencing symptoms, the visual structure of the storyboard changes. I want folks who have a diagnosis to know they are not alone. I want folks who know someone with a diagnosis to be able to understand that experience a little better. I want to invite everyone to be entertained, to have fun, fall in love with art and start a conversation."--Artist statement